Kolaborasi Multi-Stakeholder dalam Pemberdayaan Desa Wisata Sukarame, Banten: Penguatan UMKM, Pokdarwis, Kader Kesehatan Melalui Program Pengabdian Masyarakat - Marliana, Thika; Agustin, Dinni; Yulianti, Sri; Sova, Maya; M.Sholihah, Siti; Ahmadun, Ahmadun; Karsam, Karsam (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
Sukarame Tourism Village in Pandeglang Regency, Banten Province, is known as “The Land of Diversity” due to its rich natural, cultural, and professional diversity, encompassing fisherman, salted fish and bamboo fan craftsmen, teachers, MSMEs, health cadres, and Pokdarwis groups. This diversity holds great potential for inclusive and sustainable economic development. The Community Service Program (PkM), conducted on April 25–26, 2025, aimed to enhance the capacity of village communities in supporting tourism village development followed by 50 local communities. The method employed a participatory and educational approach through thematic training, entrepreneurship simulations, local potential mapping, and the formation of a cross- sector communication forum. The program outcomes indicate increased knowledge and skills among participants in areas such as digital marketing, tourism packaging, nutrition education, seafood processing, and household economic diversification. Furthermore, the initiative successfully facilitated the early formation of a village tourism forum to promote collaboration and integrated planning. These results affirm literature suggesting that community-based tourism development requires multi-stakeholder synergy, active local participation, and sustainable strategies grounded in local potential. This PkM activity recommends continued mentoring, integration with regional government programs, and the development of a community-based tourism roadmap to ensure long-term impact and sustainability. Keywords: Tourism Village, Collaboration, Empowerment, MSMEs, Digital Marketing